Penetration Test for the 3G Internet Service Provider and Free Basics Service by Facebook - Zaki, Salim M (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The number of devices connected to the Internet using mobile devices is increasing every day. Charge for mobile data over 3G and 4G networks is high in some countries which pushes users to browse the Internet through text-only service. Facebook proposed free basics service which allows users to browse Facebook for free but without showing images. This research formats the images on web pages in a method that makes images transferred over text-only networks. This allows users with low income or slow connections to surf text service over the internet with images supported. The main objective is to test the free basic service by Facebook and Internet Service Provider over 3G networks additionally proposing an image format for text-only networks. The proposed algorithm converts .png and .jpg images and post them on the Facebook page. The results from the Facebook page show images can be seen over 3G networks with free mode enabled.